The Role of Financial Literacy in Post-Disaster Financial Management of MSMEs: A Case Study in Huntap Duyu and Balaroa Sub-districts, Palu City - Irma Damaiyanti Lelewana; Vitayanti Fattah; Juliana Kadang; Rian Risendy (The Journal of Financial, Accounting, and Economics, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in post-disaster economic recovery, including in relocation areas such as Huntap Duyu and Balaroa Sub-districts in Palu City. This study aims to explore the role of financial literacy in MSME financial management practices in both sub-districts. The method used is a qualitative approach with an intrinsic case study, which includes in-depth interviews, participant observation, and documentation to obtain data on the level of financial literacy, financial management practices, and challenges faced by MSME actors. The results of the study indicate that most MSME actors in the area have a low understanding of financial literacy, which is reflected in informal and intuitive financial management practices. However, there are differences between business actors in Duyu and Balaroa, with MSME actors in Duyu being more open to financial training and assistance. This study provides theoretical contributions in the development of financial literacy in the post-disaster context and practical in designing more effective community-based economic empowerment programs. These findings are expected to be the basis for supporting institutions and policy makers in designing more relevant interventions for MSMEs in relocation areas. The right financial education program can help MSMEs improve their business resilience and economic sustainability in the future.